EDUKASI CUCI TANGAN PAKAI SABUN (CTPS) PADA ANAK SD SEBAGAI UPAYA PENCEGAHAN PENYAKIT DIARE DI DESA WAKALAMBE - Kertin Kertin; Ld Arlin; Juhulia; Herlina Rial.F; Nur Rahma (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Diarrheal disease remains one of the common health problems among elementary school children due to the low awareness of maintaining hand hygiene. This community service activity was carried out in Wakalambe Village with the aim of increasing children’s knowledge and habits regarding Handwashing with Soap (HWWS) as an effort to prevent diarrheal diseases. The selection of this topic was based on the lack of understanding among children about the proper times and methods for washing hands in daily life. The community service method was conducted through health education activities, including material presentations, demonstrations of proper handwashing steps, direct practice with students, and interactive question-and-answer sessions. The results of the activity showed that participants had a better understanding of the importance of hand hygiene and were able to practice proper HWWS techniques after receiving the education. This activity had a positive impact on increasing awareness of clean and healthy living behaviors among elementary school children. Therefore, HWWS education can serve as an effective step in preventing the spread of diarrheal diseases in schools and the community.